Premenstrual Syndrome: An Overview of the Review Analysis, and Potential Role of Herbal and Dietary Supplements - Kumari, Pooja; Saxena Pal, Rashmi; Lalitha Chaitanya, Motamarri Venkata N.; Pal, Yogendra; Punniyakotti, Saranya (Current Women's Health Reviews, 2024)
A premenstrual syndrome is a group of regular physiological, mental, emotional, and behavioral symptoms that appear periodically in the luteal phase of the menstrual cycle, and they vanish quickly with the beginning of menstruation or a few days afterward. Thus, severe premenstrual syndrome (PMS) affects 5–8% of women; the majority of these individuals also match the factors for premenstrual dysphoric disorder (PMDD). Premenstrual syndrome typically includes physical problems like headache, tiredness, indigestion, insomnia, nausea, and breast tenderness as well as symptoms associated with emotions (mood swings, anxiousness, and aggressiveness). Although the true mechanism of PMS is unknown, a number of theories point to increased sensitivity to typical hormonal changes and imbalances in neurotransmitters. A multidisciplinary team using an integrative holistic approach in the direction of an individualized strategy gradually manages PMS. The first phase entails educating women about PMS, self-screening, herbs like St John’s Wort, chaste berry, saffron; Ginkgo biloba; chamomile, evening primrose, turmeric and so on, various nutrition supplements as Vitamin B6; calcium; magnesium and lifestyle adjustments like dietary modifications; exercise; yoga; sleep hygiene. The second step involves implementing various relaxation therapies, cognitive behavioral therapy (CBT), stress reduction techniques, and acupuncture. The available treatment as various drugs like SSRIs; serotonergic antidepressants; anxiolytics and hormonal therapy that are used currently to treat PMS, exhibits unwanted side effects. Therefore, this issue and other similar gynecological conditions have been discussed and managed with herbal medicines and other natural solutions in this comprehensive piece of work.
Keywords: Premenstrual syndrome